Decoupling Oxygen and Chlorine Evolution Reactions in Seawater using Iridium‐based Electrocatalysts. Issue 18 (23rd July 2020) - Ko, Jesse S.; Johnson, James K.; Johnson, Phillip I.; Xia, Zhiyong
Abstract: A series of iridium (Ir) organometallic‐based electrocatalysts fused onto high surface‐area activated carbon using pyrolysis were prepared for the oxygen evolution reaction (OER) in seawater electrolysis. These catalysts had a low loading of Ir (<6 wt%), while also inducing atom coordination to the Ir center. The morphology and chemical composition of these electrocatalysts were analyzed by scanning electron microscopy, energy dispersive spectroscopy, and X‐ray photoelectron spectroscopy, which all showed a uniform dispersion of Ir and heteroatom‐doped moieties. To assess electrocatalytic activity, we used an artificial electrolyte comprising 0.1 M HClO4 +3.5 wt% NaCl, and found that these catalysts delivered a low overpotential of 243 mV, a low Tafel slope (92 mV dec −1 ), and a high exchange current density (1.4 mA cm −2 ). By using a headspace chlorine gas (Cl2 ) detector in situ, we discovered that a Cl2 content of 27 ppm was present. When tested in synthetic seawater, the overpotential exhibited a two‐fold increase, yet Cl2 was undetected, thus indicating favorable OER kinetics. This significant finding exemplifies the need for in situ Cl2 detection for seawater splitting research, since further insight can be derived to help guide the design of novel electrocatalysts. Abstract : Iridium organometallic‐based electrocatalysts fused onto activated carbon using pyrolysis were electroanalyzed for the oxygen evolution reaction (OER) in seawater electrolysis. To decouple competing chlorine evolution reaction (CER) and OER, we adapted a headspace chlorine gas detector to understand the electrocatalysts' propensity for chlorine gas generation in both acidic electrolyte and synthetic seawater. When tested in seawater, the overpotential exhibited a two‐fold increase compared to when tested in an acidic environment, yet chlorine was undetected, thus indicating favorable OER kinetics.